Augmented reality support for self-service automated systems - Baranovski, Igor; Stankovski, Stevan; Ostojić, Gordana; Horvat, Sabolč; Srđan, Tegeltija (Journal of Graphic Engineering and Design, 2020)
Augmented Reality (AR) is a way of looking at the real environment in which the computer-generated environment is located. The use of augmented reality changes the way we interact with the real environment. In the past few years, with the development of technology, augmented reality is gaining in importance and becoming closer to everyday users. Many companies such as Google, Sony, HTC and Samsung are investing heavily in the development of this field. Augmented reality is finding usage in various areas such as entertainment, marketing, navigation, surveillance, system maintenance, and user training. The purpose of this paper is to present the possibilities of using augmented reality systems for the needs of self-service automated systems.